Kontribuai Program Paket Masa Depan Dalam Pemberdayaan Ekonomi Perempuan Pra Sejahtera di Pedesaan - Galeh Itamaji; Witjaksono Eko Hartoto (Jurnal Bisnis dan Ekonomi, 2018)
This research aims to determine the extent to which the contribution of PMD in Economic Empowerment of Poor Women in Rural can have a positive impact on economic empowerment of poor rural women. This research used questionnaires and interviews involving 20 informants who were taken randomly in Kecamatan Limbangan as a sample. This research also uses qualitative approach as research method. The results of this research show PMD Program (Paket Masa Depan) succeeded in empowering the community economy in rural areas, especially in the area of Kecamatan Limbangan. The results of this research showed 80% of respondents feel their welfare and no longer depend on the husband's income. Based on the research and data that has been done on the contribution of PMD program in the economic empowerment of rural community, the writer can conclude that PMD program to economic empowerment of rural community can be done effectively in accordance with the target achievement.